Synthesis of Novel Methoxy Substituted Benzothiazole Derivatives and Antifungal Activity against Aspergillus Niger - Akhilesh Gupta (Journal of Global Pharma Technology, 2018)
Background Aspergillus species mainly cause a spectrum of disease ranging from airway colonization. In case of respiratory tract, aspergilloma is the most common form of pulmonary involvement, which is usually accompanied by preexisting lung disease finally architectural abnormalities most commonly stem from tuberculosis, although other associated conditions, such as sarcoidosis, bronchiectasis, and neoplasm, have been documented. Synthesis and screening of benzothiazole derivatives have great importance in heterocyclic chemistry because of its potent and significant biological activities. Methoxy substitution at benzothiazole has already proven its bioactivities in diversified areas. Methods Methoxy substituted benzothiazole derivatives were synthesized by reaction of 3- chloro-4-methoxy-aniline with potassium thiocyanate under temperature control and presence of bromine in glacial acetic acid and ammonia. Substituted nitrobenzamides then synthesized by condensation of, 2-amino-4-chloro-5-methoxy-benzothiazole with 2(3or4)-nitrobenzoylchloride acid in presence of dry pyridine and acetone. Finally, newly synthesized derivatives (K-01 to K-09) were synthesized through replacing of chlorine of nitrobenzamide by reaction with 2-nitroaniline, 3-nitroaniline, and 4-nitroaniline in presence of DMF. Analtytical characterization was performed by TLC, melting point, IR and NMR spectroscopy. Antifungal activity was performed against Aspergillus niger by cup plate method (diffusion technique) using griseoflavin as standard. Compound K-05 and K-06 showed potent antifungal activity against Aspergillus niger while compound K-01 and K-03 showed moderate inhibitory activity at both concentrations 50µg/ml and 100µg/ml as compared to standard. Conclusion In the present work efforts have been made to synthesized methoxy substituted benzothiazole derivatives and screened for antifungal activity. Compound K-05 and K-06 found as most active against Aspergillus niger.Keywords: Methoxy-benzothiazole, Benzothiazole, Antifungal activity, 2-substituted benzothiazole, Cyclization of benzothiazole, Aspergillus niger.